CALCULATION OF ENERGY EFFICIENCY OF PHOTOCELL OF THE SOLAR STATION - Taylanov, Nizom; Khamdamov, Begali; Egamqulova, Zilola (Физико-технологического образование, 2021)
A methodology has been developed for calculating the power and efficiency of solar power plants and its elements, allowing to take into account the change in load during the day and thereby accurately determine the required battery capacity